1994
DOI: 10.1172/jci117591
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of the intestinal parasite Giardia lamblia by a dietary lectin is associated with arrest of the cell cycle.

Abstract: Giardia lamblia, a cause of diarrheal disease throughout the world, is a protozoan parasite that thrives in the small intestine. It is shown here that wheat germ agglutinin (WGA), a naturally occurring lectin widely consumed in normal human diets, reversibly inhibits the growth of G. lamblia trophozoites in vitro, and reduces infection by G. muris in the adult mouse model of giardiasis. The inhibitory effect was dose related, not associated with cytotoxicity and reversed by N-acetyl-D-glucosamine in accordance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…5), with no DNA replication detected even after 48 h in culture. These findings contrast with those previously described for lectins, which led to arrest in a later phase (G 2 /M) of the cell cycle (27). Interestingly, differentiation into cysts takes place from the G 2 phase (2), and thus the extracellular factors produced by La1, can prevent giardia from producing cysts that in turn will diminish the spreading of the parasite.…”
Section: Discussioncontrasting
confidence: 77%
“…5), with no DNA replication detected even after 48 h in culture. These findings contrast with those previously described for lectins, which led to arrest in a later phase (G 2 /M) of the cell cycle (27). Interestingly, differentiation into cysts takes place from the G 2 phase (2), and thus the extracellular factors produced by La1, can prevent giardia from producing cysts that in turn will diminish the spreading of the parasite.…”
Section: Discussioncontrasting
confidence: 77%
“…Through the course of this work, we observed that previously published flow cytometry DNA distributions of Giardia trophozoites showed wide unresolved peaks which were difficult to interpret (7,17,21). Recent advances in Giardia flow cytometry protocols (4) greatly improved peak resolution but were not readily reproducible in our laboratory.…”
Section: Resultsmentioning
confidence: 93%
“…The effect of alcohol treatment on G. duodenalis infections is much greater than that of oral consumption of whole wheat and/or wheat germ, which contain WGA and are common components of the human diet. In a rodent model and in human infections, WGA, which binds to short N-glycans of G. duodenalis and reduces excystation in vitro, showed modest reduction in cysts shed and in symptoms (humans) (37)(38)(39). A commercial alcohol-based hand sanitizer killed E. invadens cysts directly applied to the hands, validating the findings when E. invadens cysts were treated with alcohols in a microcentrifuge tube and dried in the rotary evaporator.…”
Section: Discussionmentioning
confidence: 54%